2011
DOI: 10.1371/journal.pone.0022959
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HTRA1 Leads to Ultrastructural Changes in the Elastic Layer of Bruch's Membrane via Cleavage of Extracellular Matrix Components

Abstract: Variants in the chromosomal region 10q26 are strongly associated with an increased risk for age-related macular degeneration (AMD). Two potential AMD genes are located in this region: ARMS2 and HTRA1 (high-temperature requirement A1). Previous studies have suggested that polymorphisms in the promotor region of HTRA1 result in overexpression of HTRA1 protein. This study investigated the role of HTRA1 overexpression in the pathogenesis of AMD. Transgenic Htra1 mice overexpressing the murine protein in the retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 46 publications
5
118
0
Order By: Relevance
“…It cleaves and inhibits TGF beta, and several extracellular matrix proteins, including fibronectin and amyloid precursor protein (Beaufort et al., 2014; Grau et al., 2005; Oka et al., 2004). Also, when HTRA1 is overexpressed in mice, the elastic network of extracellular matrix becomes fragmented between the RPE and the choroid (Vierkotten, Muether & Fauser, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…It cleaves and inhibits TGF beta, and several extracellular matrix proteins, including fibronectin and amyloid precursor protein (Beaufort et al., 2014; Grau et al., 2005; Oka et al., 2004). Also, when HTRA1 is overexpressed in mice, the elastic network of extracellular matrix becomes fragmented between the RPE and the choroid (Vierkotten, Muether & Fauser, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…AMD pathogenesis and previous HTRA1 experiments related to AMD have been performed and discussed in relation to the RPE (8,16,17). However, immunostaining of HTRA1 in mouse retinas in the present study showed that the majority of transcription occurs in the photoreceptor cell layer (Fig.…”
Section: Characterization Of Htra1 Regulatory Elementsmentioning
confidence: 43%
“…A recent report using transgenic mice overexpressing human HTRA1 in the RPE showed that PCV-like capillary structures could be observed in the choroid. Vierkotten et al (17) also observed fragmentation of the elastic layer in Bruch's membrane, and Jones et al (16) reported branching of choroidal vessels, polypoidal lesions, and severe degeneration of the elastic lamina or tunica media of choroidal vessels in the same model. When HtrA1 expression was driven by the CAG promoter in a transgenic mouse model, an even more severe phenotype was induced compared with previous reports of AMD patient-like choroidal neovascularization (23).…”
Section: Characterization Of Htra1 Regulatory Elementsmentioning
confidence: 93%
See 1 more Smart Citation
“…Elastin is a principal component of Bruch's membrane, and reduced levels of functional fibulin-5 protein in the extracellular matrix may impair the normal assembly of elastin within Bruch's membrane (Stone et al 2004). Interestingly, overexpression of HTRA1, which has been associated with AMD pathogenesis (Yang et al 2010), has been shown to alter elastogenesis in Bruch's membrane through cleaving fibulin-5 (Yang et al 2010;Vierkotten et al 2011). Alternatively, interference with another function of fibulin-5 (for example, integrin-mediated cell attachment) may contribute to the pathogenic mechanism underlying fibulin-5 variants (Stone et al 2004).…”
Section: Fibulin-5 (Fbln5)mentioning
confidence: 99%